Optimization of Hydrogen Internal Combustion Engines Equipped with Turbocompound Technology for Enhanced Performance and Efficiency - Pier Paolo Brancaleoni; Enrico Corti; Federico Di Prospero; Davide Di Battista; Roberto Cipollone; Vittorio Ravaglioli (Energies)
Hydrogen Internal Combustion Engines (H2ICEs) offer significant potential in reducing the CO2 emissions of the heavy-duty transport sector in the pursuit of the European Green Deal targets. However, the challenges associated with hydrogen energy density require advanced technologies for fuel efficiency enhancement. Hybrid powertrains, equipped with innovative energy recovery systems, allow optimizing the engine working point while recovering otherwise wasted energy. In particular, Turbocompound (TCo) systems allow recovering the energy content in the exhaust gases, improving the overall efficiency of the powertrain. Optimizing both engine operation and TCo recovery presents a significant challenge, as it requires balancing the dynamic interaction between the engine’s combustion process and TCo (which increases backpressure). This paper presents a novel approach aimed at optimizing the performance of a hybrid hydrogen-fueled internal combustion engine by integrating a TCo system. The TCo allows extracting a 9 kW extra power peak with respect to the baseline configuration. The performance assessment of the optimized working point for series hybrid powertrains underscores the capability of the strategy to reduce hydrogen consumption up to 6.8%.